Some Socio-Psychological Aspects of Birth-Rate - Baršys, Vytautas (Problemos, 1981)
An analysis of reproductive orientations and motives is presented in the article. The author comes to the conclusion that reduction of birth-rate and the spread of small families are related to the decrease of the need for children in a family. Thus to increase birth-rate, it is insufficient to influence the conditions stimulating the birth of a second and a third child, but it is found to be imperative to form the need itself. The forming of this necessity in a family for two-three children, whose appearance is essential in providing a usual reproduction of population, is considered the major task in controlling socio-demographic processes.